2013
DOI: 10.1155/2013/720728
|View full text |Cite
|
Sign up to set email alerts
|

Phyllanthus emblicaL. Enhances Human Umbilical Vein Endothelial Wound Healing and Sprouting

Abstract: Endothelial dysfunction is the hallmark of impaired wound healing and increased risk of cardiovascular disease. Antioxidants from natural sources decrease oxidative stress and protect against cellular damage caused by reactive oxygen species (ROS). In this study, we examined the antioxidant constituents and capacity of Phyllanthus emblica L. (PE) fruit in freeze-dried power form. The pharmacological properties of PE were investigated using human umbilical vein endothelial cells (HUVECs) in the aspects of endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…The scratch wound assay was performed in low serum (1% FBS) as previously described [15]. For the scratch wound assay, HUVECs were seeded in six-well plates at the density of 5000 cells/cm 2 and cultured until reaching 100% confluence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scratch wound assay was performed in low serum (1% FBS) as previously described [15]. For the scratch wound assay, HUVECs were seeded in six-well plates at the density of 5000 cells/cm 2 and cultured until reaching 100% confluence.…”
Section: Methodsmentioning
confidence: 99%
“…HUVECs were obtained from trypsin extraction using the method described previously [ 15 ]. Briefly, human umbilical cords were collected under a sterile condition from the labor room of the university hospital and processed within 48 h. Cords were washed with phosphate buffer saline (PBS) and enzyme digestion (0.1% collagenase) was performed at 37 °C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Focusing on the fruit, it has been demonstrated that the fruits of PE are rich in phenolics (She et al, 2013) and possess antioxidant activities (Chalise et al, 2010;Sawant et al, 2010). In addition, PE fruits have been proven to have many therapeutic properties (Krishnaveni and Mirunalini, 2010;Chularojmontri et al, 2013). PE fruits have been used for anti-inflammation, anti-aging, and anti-melanogenesis.…”
mentioning
confidence: 99%
“…Higher levels of tissue ascorbic acid, alpha-tocopherol, reduced glutathione, superoxide dismutase, catalase and glutathione peroxidase support the fact that P. emblica promotes antioxidant activity at the wound site in excision wound model [104]. Again, aqueous extract of the fruit of P. emblica (0.1 μg/mL) in scratch assay using human umbilical vein endothelial cells (HUVEC) was shown to promote endothelial cell function and wound healing by significantly (p < 0.05) promoting NO production, endothelial wound closure, endothelial sprouting, and VEGF mRNA expression which provides further evidence to support the traditional use of P. emblica as a wound healing agent [105].…”
Section: Euphorbiaceamentioning
confidence: 71%